Image enhancement based on neuro-fuzzy gradient profile clustering - Ngernplubpla Jaturon; Chitsobhuk Orachat (My University, 2018)
This paper proposes a technique for image enhancement using Neuro-fuzzy based gradient profile generation to reconstruct the high resolution image from a single low resolution one. The natural gradient priors are collected and their statistics are analyzed and learned through Neuro-fuzzy model. The model adopts powerful data adaptation from neural network and combines with fuzzy system to enhance the ability in knowledge interpretation and explanation in terms of natural language. The triplet gradient profile is then generated as a result. The gradient profile results are used to regulate the Gaussian weighted sum filter in enhancement process. Then, all the weights were appropriately adapted according to gradient priors. From the experimental results, it can be seen that the proposed algorithm can greatly compensate the contrast and noise distortion in the low resolution image and demonstrate successful recovery of the high resolution image with quantitatively and perceptually performance improvement.   Key words: Image enhancement, super resolution, neuro-fuzzy clustering, gradient profile generation, gradient priors.
Keywords: Distortion (music); Advanced Image Processing Techniques